Information technology. International standardized profiles FVT2nn. Virtual terminal basic class. Register of control object type definitions. FVT232. Paged FEPCO (Field Entry Pilot Control Object) No. 1 Part 11, (15th March 1995) - British Standards Institution,
No abstract available